A Comparative Study of Alkalined and Plain Local Anesthetic on Onset, Duration and Quality of Bracheal Plexus Block by Supraclavicular Approach. - Yadav, Rajesh Kumar; Thapa, Ajay Singh; Sah, Rakesh (Birat Journal of Health Sciences, 2022)
Introduction: Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in term of such damage. The relief from pain is the essence of anesthesia. Peripheral nerve blocks provide longer and more localized pain relief than neuraxial techniques while also avoiding the side effects of systemic medication. This study was aimed to find the effectiveness of Study solution (addition of Sodium bicarbonate to 0.375% Bupivacaine) on onset time, duration and quality of Brachial Plexus Block. Material and methods: This study was conducted among 60 different patients undergoing surgical procedure of the upper limb. They were categorized into two different groups. The first group (Group 1), 30 patients received Brachial Plexus block with 30 ml of study solution (0.375% Bupivacaine with 2 ml of Sodium bicarbonate7.4%). The second group (Group 2) received 30 ml of 0.375 % plain bupivacaine only and the differences in onset, duration and quality of blockade were studied. Result: The similarity of age between the two groups can be seen. In Group 1 the mean onset time of sensory blockade was 9.43 minutes and motor blockade was 10.43 minutes when compared to Group 2 having sensory onset of minutes 23.93 and motor onset of 26.33 minutes. Similarly, In Group I the mean duration of sensory blockade was 477.67 minutes and motor blockade were 467.67 minutes when compared to Group 2 having sensory duration of 215.67 and motor duration of 205.67 minutes. The quality of sensory blockade was also better in group1 (P-Value:0.006). Conclusion: Addition of Sodium bicarbonate to bupivacaine had significant clinical advantage over plain bupivacaine on onset time, duration and quality of sensory and motor blockade in brachial plexus block.